Effects Of Trigona Apicalis Propolis Ethanolic Extract On Antioxidant Activities And Wound Healing Using Human Gingival Fibroblast Cells - Rosli, Nur’liyana (2019)
Propolis is a resinous substance found in beehives. It provides beneficial effects on human health and has been used to treat many diseases since ancient times. The objectives of this study were to analyse the chemical profile of the propolis extract and to quantify the major chemical compounds of the propolis extract using total phenolic and total flavonoid content methods, to determine the antioxidant activities of the propolis extract using DPPH and ABTS colourimetric assays, and to assess the wound healing properties of propolis extract using scratch assay. The ethanolic extract of propolis was subjected to HPLC analysis to analyse its phytochemical profile. The propolis extract was later tested for antioxidant capacities by using DPPH and ABTS radical scavenging assay and FRAP assay. TPC and TFC were performed to determine the correlation with its antioxidant activities which show the strong correlation, r2 > 0.9. Scratch assay was later tested for wound healing properties in the gingival fibroblast cell lines based on dose dependent and time dependent manner. The results demonstrated that the antioxidant activities of propolis extract were dose dependent. The IC50 for DPPH and ABTS assay were 1.90 mg/ml and 0.57 mg/ml, respectively. Correlation values of TPC and TFC against DPPH, ABTS and FRAP indicated that the antioxidant activities of propolis extract used in this study could be mainly influenced by the phenolic and flavonoid content.